Letter to the Editor—An Algorithm for Ranking all the Assignments in Order of Increasing Cost - Murty, Katta G. (Operations Research, 1968)
The Hungarian method gives an efficient algorithm for finding the minimal cost assignment. However, in some cases it may be useful to determine the second minimal assignment (i.e., the best assignment after excluding the minimal cost assignment) and in general the kth minimal assignment for k = 1, 2, …. These things can easily be determined if all the assignments can be arranged as a sequence in increasing order of cost. This paper describes an efficient algorithm for such a ranking of all the assignments. The maximum computational effort required to generate an additional assignment in the sequence is that of solving at most (n − 1) different assignment problems, one each of sizes 2, 3, …, n.